Narrativas (auto) biográficas de formação continuada dos professores de educação física - Luiz, Igor Câmara (2014)
Investigates the continued formation in Physical Education taking as source the (auto) biographical narratives of fourteen Physical Education teachers that works in Elementary School in three counties of Grande Vitória –ES. It is characterized as a research with (auto) biographical narratives (PEREZ, 2003; SOUZA, 2010), having as source: questionary, focal group, interview, talk circle and the participant observation with register in field diary. The study is structured in three articles that articulates themselves. In the first of them, we analyze the meanings that teachers attribute to continued formations. In the second, analyzes the productive consumptions (CERTEAU, 1994) that teachers produces in and from formation contexts. With the intention of approaching University to Elementary School and sign possibillities of policies on this theme, we analyze, in third chapter, the formation held at the Centro de Educação Física (CEFD) in Universidade Federal do Espírito Santo (UFES), by the Instituto de Pesquisas em Educação e Educação Física (PROTEORIA). Based in chapters 1 and 2, we perceived that the meanings and appropriations that teachers make from and with these places takes in consideration the defense that they make of Physical Education as curricular component, of Professional identity and field. They also take into account the singularities of each context, the concerns and individual necessities of teachers. Based on third article we observe the necessity of establish, among formation context, the opening of dialogue with experiences of pedagogical actuation of teachers as elements of collective reflection. It would be up to University and public administrations to foment the signification of this knowledge with teachers, using researches and investigations about and with the pedagogical practices in a production of other theories movement.